PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 2 TEBO - Lady Kidung Asmoro (Jurnal Edukasi dan Penelitian Matematika, 2021)
The ability to solve mathematical problems is one of the goals that students must achieve in learning mathematics. But in fact the mathematical problem-solving abilities possessed by students of class XI MIPA SMA Negeri 2 Tebo are still low. Efforts that can be made to improve mathematical problem solving abilities are to apply the Think Talk Write (TTW) type of cooperative learning model. This type of research is the Quasy Experiment and Randomized Control Group Only Design chosen as the research design model. The research results show that there is an effect of the application of the think talk write type cooperative learning model on the mathematical problem solving abilities of students. Thus, the mathematical problem solving abilities of students who learn with the Think Talk Write type of cooperative learning model are better than the mathematical problem solving abilities of students who learn using the direct learning model. Keywords — mathematical problem solving, cooperative learning, think talk write